2021
DOI: 10.3389/fcimb.2021.647020
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Tick Inward Rectifier Potassium Channels and Their Potential as Targets to Innovate Control Technologies

Abstract: This study was conducted to enhance the identification of novel targets to develop acaricides that can be used to advance integrated tick-borne disease management. Drivers for the emergence and re-emergence of tick-borne diseases affecting humans, livestock, and other domestic animals in many parts of the world include the increased abundance and expanded geographic distribution of tick species that vector pathogens. The evolution of resistance to acaricides among some of the most important tick vector species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Additional vaccine development opportunities exist, with a current focus on improving identification and characterization of ixodid antigens that can then be generated in the laboratory [ 254 ]. Further, relatively recent research has identified compounds within ixodid saliva that might play functional roles in vaccine development [ 255 ]. Ixodid saliva warrants scrutiny because it contains proteins that facilitate transmission of ixodid-borne pathogens through the salivary protein’s anti-inflammatory, anticoagulant, and immunosuppressive properties [ 255 , 256 ].…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional vaccine development opportunities exist, with a current focus on improving identification and characterization of ixodid antigens that can then be generated in the laboratory [ 254 ]. Further, relatively recent research has identified compounds within ixodid saliva that might play functional roles in vaccine development [ 255 ]. Ixodid saliva warrants scrutiny because it contains proteins that facilitate transmission of ixodid-borne pathogens through the salivary protein’s anti-inflammatory, anticoagulant, and immunosuppressive properties [ 255 , 256 ].…”
Section: Vaccinesmentioning
confidence: 99%
“…Further, relatively recent research has identified compounds within ixodid saliva that might play functional roles in vaccine development [ 255 ]. Ixodid saliva warrants scrutiny because it contains proteins that facilitate transmission of ixodid-borne pathogens through the salivary protein’s anti-inflammatory, anticoagulant, and immunosuppressive properties [ 255 , 256 ]. Several ixodid salivary gland proteins (TSLPI, Salp15, tHRF, and TIX-5) have, as well, been identified as novel candidates for an anti-ixodid vaccine [ 257 ].…”
Section: Vaccinesmentioning
confidence: 99%